P76 The effect of outside temperature on daily physical activity in COPD patients. (19th November 2012) - Alahmari, AD; Donaldson, GC; Patel, ARC; Kowlessar, BS; Mackay, AJ; Singh, R; Wedzicha, JA
Abstract : Introduction: COPD is characterised by breathlessness, leading to reduced physical activity. Breathlessness varies dependent upon the degree and intensity of physical activity (1). Common logic dictates that weather variation such as temperature and sunshine could influence physical activity in the general population, especially walking. The aims of this study were to evaluate the effect of weather variation on daily activity and the variation in activity during the days of the week in COPD patients. Methods: Fifty-five stable COPD outpatients from the London COPD cohort wore a pedometer (Yamax Digi-Walker SW-200) daily for 30 days during waking hours. We excluded exacerbating patients and those using walking sticks or oxygen. All patients were asked to record their step count on daily diary cards. Weather data for London Heathrow were obtained with permission from the British Atmospheric Data Centre. Stable COPD was defined as having no symptom-defined exacerbations in the preceding six weeks and subsequent two weeks, according to prospectively-collected diary cards, with no change in long-term inhaled and oral medications in the preceding two weeks. Results: The clinical characteristics of the 55 patients were mean (±SD) age 70.3 (8.7) years; FEV1% predicted 51.0% (±14.1); male gender 67%; current smoker 25%, BMI 27.2 kg/m2. The mean (±SD) daily step count was 4327 (±2944). COPD patients were more active as temperatures increased (Figure 1A ) and on sunny as opposed to no sunshine days (Figure 1B, p<0.001). Figure 1C shows that mean weekday activity is significantly higher than mean weekend activity (p<0.001), mainly due to less activity on Sunday. Conclusion: Daily activity in stable COPD markedly affected by outdoor temperature and sunshine and patients had highest activity during weekdays. Further work is required to ascertain whether some patients are more active than others. Reference: Pitta F et al ., Quantifying Physical Activity in Daily Life with Questionnaires and Motion Sensors in COPD, ERJ 27, no. 5 (April 2006): 1040–1055.